Transgenerational transmission of the Glossina pallidipes hytrosavirus depends on the presence of a functional symbiome. - Drion G Boucias; Henry M Kariithi; Kostas Bourtzis; Daniela I Schneider; Karen Kelley; Wolfgang J Miller; Andrew G Parker; Adly M M Abd-Alla (PLoS ONE)
The vertically transmitted endosymbionts (Sodalis glossinidius and Wigglesworthia glossinidia) of the tsetse fly (Diptera: Glossinidae) are known to supplement dietary deficiencies and modulate the reproductive fitness and the defense system of the fly. Some tsetse fly species are also infected with the bacterium, Wolbachia and with the Glossina hytrosavirus (GpSGHV). Laboratory-bred G. pallidipes exhibit chronic asymptomatic and acute symptomatic GpSGHV infection, with the former being the most common in these colonies. However, under as yet undefined conditions, the asymptomatic state can convert to the symptomatic state, leading to detectable salivary gland hypertrophy (SGH(+)) syndrome. In this study, we investigated the interplay between the bacterial symbiome and GpSGHV during development of G. pallidipes by knocking down the symbionts with antibiotic. Intrahaemocoelic injection of GpSGHV led to high virus titre (10(9) virus copies), but was not accompanied by either the onset of detectable SGH(+), or release of detectable virus particles into the blood meals during feeding events. When the F1 generations of GpSGHV-challenged mothers were dissected within 24 h post-eclosion, SGH(+) was observed to increase from 4.5% in the first larviposition cycle to >95% in the fourth cycle. Despite being sterile, these F1 SGH(+) progeny mated readily. Removal of the tsetse symbiome, however, suppressed transgenerational transfer of the virus via milk secretions and blocked the ability of GpSGHV to infect salivary glands of the F1 progeny. Whereas GpSGHV infects and replicates in salivary glands of developing pupa, the virus is unable to induce SGH(+) within fully differentiated adult salivary glands. The F1 SGH(+) adults are responsible for the GpSGHV-induced colony collapse in tsetse factories. Our data suggest that GpSGHV has co-evolved with the tsetse symbiome and that the symbionts play key roles in the virus transmission from mother to progeny.